Permukiman Musiman Sebagai Bentuk Adaptasi Hunian Petani Subsisten di Pedesaan - Shabrina Tamimi; Dwita Hadi Rahmi; Ikaputra - (Unika Soegijapranata Semarang, 2019)
Society lives in a place called settlement. Peasants are one of community which live in settlement specifically in rural settlement due to the wider area for cultivating land. The main characteristic of the peasant is the independence in providing their own food source. Instead of buying from market, peasants will provide food source needs from their subsistence farming. Hence, peasants tend to live casually and cultivate in household scale. Peasants have adjustments and adapt to the particular form of settlement in rural area. One of settlement form is when they have two types of house: the main house and the temporary house. The temporary house tends to be built close to the field and occupied during fertile season. This type of house can be catagorized as seasonal settlement and is an adaptation of peasant’s life in term of economy, environment, and social organization